2019
DOI: 10.1371/journal.ppat.1008232
|View full text |Cite
|
Sign up to set email alerts
|

Ecotin, a microbial inhibitor of serine proteases, blocks multiple complement dependent and independent microbicidal activities of human serum

Abstract: Ecotin is a serine protease inhibitor produced by hundreds of microbial species, including pathogens. Here we show, that ecotin orthologs from Escherichia coli, Yersinia pestis, Pseudomonas aeruginosa and Leishmania major are potent inhibitors of MASP-1 and MASP-2, the two key activator proteases of the complement lectin pathway. Factor D is the key activator protease of another complement activation route, the alternative pathway. We show that ecotin inhibits MASP-3, which is the sole factor D activator in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 67 publications
1
41
0
2
Order By: Relevance
“…In contrast, ErpB and ErpQ bind to both C1r and C1s but selectively recognize activated forms of the proteases (Figs 2, S5). Further, we showed that ErpQ in incapable of blocking C1r activity (Fig S7 Finally, ErpQ did not prevent cleavage of small peptide substrates, and is unusual among microbial-derived serine protease inhibitors, such as ecotin or BBK32 (49), which typically target the active site (79,80).…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, ErpB and ErpQ bind to both C1r and C1s but selectively recognize activated forms of the proteases (Figs 2, S5). Further, we showed that ErpQ in incapable of blocking C1r activity (Fig S7 Finally, ErpQ did not prevent cleavage of small peptide substrates, and is unusual among microbial-derived serine protease inhibitors, such as ecotin or BBK32 (49), which typically target the active site (79,80).…”
Section: Discussionmentioning
confidence: 94%
“…The regulator of the mucoid phenotype rmp genes were detected in K. pneumoniae ( n = 14/218; 6.4%) and K. quasipneumoniae ( n = 1/83; 1.2%). Ecotin has been described as being able to modulate the host immune response [ 56 ] and was detected in isolates belonging to all species ( n = 445/548; 81.2%).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strategies to avoid neutrophil-mediated killing include launching a general survival response, avoiding contact, preventing phagocytosis, surviving inside the neutrophil, and inducing cell death [ 10 , 11 ]. Specific countermeasures against the action of proteases are the production of protease inhibitors, including serine protease inhibitors such as ecotin [ 12 ], or masking proteolytic cleavage sites through glycosylation of protease target proteins [ 13 ]. Protein glycosylation is the most common post-translational modification in nature and exists in all three domains of life.…”
Section: Introductionmentioning
confidence: 99%
“…coli as a periplasmic protease inhibitor that exhibits a broad specificity toward exogenous serine proteases including trypsin, chymotrypsin, factor Xa, NE, kallikrein, urokinase and factor XII, but not against metallo-, aspartyl and sulfhydryl proteases, or its own proteases [ 28 32 ]. Ecotin homologs have since been found in more than 300 organisms, predominantly in Gram-negative bacterial pathogens such as Pseudomonas aeruginosa , Shigella flexneri , Yersinia pestis , Burkholderia pseudomallei and Klebsiella pneumoniae [ 12 , 31 33 ], but also in two eukaryotic protozoan parasites within the Trypanosomatidae genus ( Leishmania major and Trypanosoma cruzi [ 12 , 34 , 35 ]), and in some plant pathogens e. g. Pantoea citrea [ 31 ]. In the latter case, ecotin was found to be less potent in binding to NE when compared to the E .…”
Section: Introductionmentioning
confidence: 99%